1997
DOI: 10.1177/074171369704700202
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Persistence on Literacy Learning in Adult Education

Abstract: Limitations in sampling and research design in past studies have hampered understanding of adult education's impact on the acquisition of basic skills. The present study used a selection bias weighting adjustment and ordinary regression techniques in a path analysis approach to identifying variables which directly and indirectly influence reading achievement in adult literacy programs. A major focus of the study was estimating the effect of student persistence (hours of instruction) on literacy outcomes in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Rose and Wright (2006) examined the national reporting system (NRS) data of three states and found that at 100 to 110 hours of participation, 50% of students were likely to show a one NRS level 12 increase or pass the general equivalency diploma (GED) test. Fitzgerald and Young (1997) analyzed data on the 614 students (out of 22,000) in a Development Associates (1993) study who had both a pretest and a posttest reading score. They found a relationship between hours of instruction and learning gains for immigrants learning English, but not for adult basic education (ABE) and adult secondary education (ASE) students.…”
Section: E F I N I T I O N O F P E R S I S T E N C Ementioning
confidence: 99%
“…Rose and Wright (2006) examined the national reporting system (NRS) data of three states and found that at 100 to 110 hours of participation, 50% of students were likely to show a one NRS level 12 increase or pass the general equivalency diploma (GED) test. Fitzgerald and Young (1997) analyzed data on the 614 students (out of 22,000) in a Development Associates (1993) study who had both a pretest and a posttest reading score. They found a relationship between hours of instruction and learning gains for immigrants learning English, but not for adult basic education (ABE) and adult secondary education (ASE) students.…”
Section: E F I N I T I O N O F P E R S I S T E N C Ementioning
confidence: 99%
“…Prior studies indicated education and age were common predictors of learner outcomes in AE programs (e.g., Alamprese, 2003;Boudett & Friedlander, 1997;Edwards, 2003;Fitzgerald & Young, 1997;Moore & Stavrianos;Snow & Strucker, 2000;Wayman, 2001). Other studies associated adult literacy with other individual characteristics, such as socioeconomic status, employment, and earnings (e.g., Council for Advancement of Adult Literacy [CAAL], 2003;Kirsch, et al, 1993;Moore & Stavrianos;Snow & Strucker); learning disabilities (e.g., Alamprese;Corley & Taymans, 2002;Elliott & Hayward, 1996;Fowler & Scarborough, 1993;Moore & Stavrianos;Snow & Strucker) and gender (e.g., Beder, 1999;Smith, 1996;Wayman).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reasons include work responsibilities and family responsibilities (AlBarwani & Kelly, 1985;Bean et al, 1989;Malicky & Norman, 1994). Program services and the way students are served are also issues (Fitzgerald & Young, 1997, Millar & So, 1998Purcell-Gates et al, 2000;Quigley, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Fitzgerald and Young (1997) found that initial ability, individualized curriculum, and the use of full time staff were the main influence on improving literacy of ABE students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation